Chemotherapy in advanced gastric cancer: a controlled, prospective, randomised multi-centre study. Issue 9 (September 1979) - Rake, M O; Mallinson, C N; Cocking, J B; Cwynarski, M T; Fox, C A; Wass, V J; Diffey, B L; Jackson, G A
Abstract : Seventy-six patients with advanced gastric adenocarcinoma were studied in a prospecitive, randmoised, controlled trial using vincristine, methotrexate, cyclophosphamide, and 5-fluorouracil in an initiation course and mitomycin-C with 5-fluorouracil as maintenance therapy. Thirty-seven patients were inoperable and 39 had the primary tumour resected with histological evidence of residual disease. Survival in the inoperable group was short and showed no significant difference between treated and control patients. The median survival times for treated and control groups were 9.5 and 9.0 weeks respectively. In the resected patients there was no difference in ultimate overall survival between the groups but up to 20 weeks there was a suggestion that the probability of survival in treated patients was higher (P = 0.06). The patients were well-matched and it is concluded that chemotherapy has had an early effect but that a further trial with more detailed stratification, particularly of staging and histological grade, is needed. No patient received treatment for longer than two years and unacceptable toxicity occurred in only two patients. Nausea occurred more frequently in the treated group but was short-lived and clinically manageable.